Exploring the “Historical Records–Architectural Remains” Model of Built Heritage Under Technological Support - Zhiyuan Chen; Muge Huang; Zhishuo Qu; Yichen Lu; Kaida Chen (Buildings, 2025)
Taking Renhezhuang in Yongtai, Fujian, as a case study, this paper explores a research framework that integrates historical records with architectural remains under technological support. Renhezhuang not only preserves relatively complete partition documents but also retains a clear spatial configuration, providing ideal conditions for comparative analysis between textual records and physical structures. By employing space syntax, daylighting simulation, and ventilation modeling, this study links the logic of property allocation recorded in documents with the spatial organization of the building. The results reveal that the distribution of living units in Renhezhuang did not pursue strict equality; rather, it achieved balance through differentiated allocation, reflecting the coordination mechanisms of a traditional lineage society under limited resources. This study not only proposes a methodological framework that integrates textual evidence, spatial remains, and technical tools, but also underscores the sociological significance of built heritage as an entry point for understanding social order. The findings offer valuable insights for both heritage conservation and the study of socio-spatial dynamics.